2022
DOI: 10.1155/2022/8334397
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Acupuncture-Moxibustion Clinical Practice Guidelines among Clinical Practitioners: A Systematic Review of Quality Assessment Studies

Abstract: Acupuncture clinical practice guidelines are authoritative medical recommendations developed by evaluating and integrating acupuncture-related evidence. However, their synthesis and dissemination are not integrated, and clinical practitioners require more credible effective evidence. The study aim was to systematically review problems disseminating acupuncture clinical practice guidelines to clinical practitioners, to facilitate evidence dissemination. This systematic review included searches of PubMed, EBSCO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…A recent systematic review exploring the problems of disseminating acupuncture clinical practice guidelines to clinicians identified important issues; lack of guideline standardization, unclear target population, mismatch between guidelines and clinical practice environment, lack of reliable health economics evaluation, poor quality content, lack of linkage between recommendations and evidence [21]. They concluded that evidence evaluation should be standardized and relevant to clinical practice [21].…”
mentioning
confidence: 99%
“…A recent systematic review exploring the problems of disseminating acupuncture clinical practice guidelines to clinicians identified important issues; lack of guideline standardization, unclear target population, mismatch between guidelines and clinical practice environment, lack of reliable health economics evaluation, poor quality content, lack of linkage between recommendations and evidence [21]. They concluded that evidence evaluation should be standardized and relevant to clinical practice [21].…”
mentioning
confidence: 99%